Acid mine drainage (AMD) treatment: Neutralization and toxic elements removal with unmodified and modified limestone - Iakovleva, E.; Mäkilä, E.; Salonen, J.; Sitarz, M.; Wang, Shaobin; Sillanpää, M. (Elsevier, 2014)
Limestones and their modifications from Nordkalk Corporation (Finland) flotation fines (FF) and filter sand (FS) as potential adsorbents for AMD treatment and wastewater purification from Cu, Fe, Zn and Ni ions were studied. Limestones were capable of binding significant amounts of Cu and Fe from synthetic AMD solutions and wastewater, while unmodified limestones were not good for Zn and Ni removal. Two methods of surface area modification were suggested. The first one with 2 M solution of NaCl and the second one with wastewater from Norilsk Nickel Harjavalta. The structure of materials and their surface area were characterized by SEM, EDX, MIR spectroscopy and nitrogen adsorption methods. Optimal amount of adsorbents for different model and real solutions was found. Adsorption kinetics showed that the adsorption equilibrium was reached within approximately 8 h. The kinetic data fits to a pseudo second order model with correlation coefficients greater than 0.999. The adsorption capacity was the highest at solution pH range of 6–7. Langmuir, Toth and Sips models were used to fit the adsorption isotherms. Based on the parameters calculated from models, the adsorption capacity decreased in the order of Cu > Fe > Zn > Ni for FF and Fe > Cu > Zn > Ni for FS. The research showed that the proposed modified limestones can be successfully used for AMD neutralization and removal of Cu(II), Fe(III), Zn(II) and Ni(II).